Digital Financial Bookkeeping Training for MSME Entrepreneurs - Damayanti, Misvia; Putra, Purnama; Khoiriyah , Ummi; Widyowati, Dian Desty (Santoso Academy Network, 2024)
The service activity aims to provide outreach, training, and assistance to MSMEs in Sukabungah Village on creating digital financial bookkeeping. Effective bookkeeping is crucial for business progress, enabling MSMEs to track financial flows, income, and profits accurately. Observations reveal that while MSME actors in Sukabungah Village engage in bookkeeping, it is not performed optimally. To address this, the service team implemented a digital bookkeeping training program using the